Case Study of The Phubbing Action of UIN Sunan Kalijaga Students in An Online Lecture - Wahyu Hidayat; Aninditya Sri Nugraheni (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2021)
The purpose of this study is to describe and reveal the impact of excessive smartphone use, which then leads to phubbing. This research study was conducted in May 2020 on 30 students of Uin Sunan Kalijaga as respondents or research subjects. This type of research is qualitative research and interviews with all research subjects, and literature review. The results of the study were recorded that 92% of 27 respondents revealed that a phubber did not give appreciation and was more likely to underestimate the other person. So, planting and practicing Pancasila values in everyday life is very important to carry out. This is so that each individual can fortify and organize himself against wise smartphone use. Then it is hoped that through this research study, students as the nation's next generation will realize the impact of excessive smartphone use on social life.